Copy number variations of SHANK3 and related sensory profiles in Egyptian children with autism spectrum disorder. (July 2020) - Meguid, Nagwa A.; Eid, Ola M.; Reda, Mona; Elalfy, Dina Y.; Hussein, Fatma
Highlights: ASD children exhibit co-occurring sensory processing problems, and hyper- or hyporeactivity to sensory input. Chromosomal rearrangements, copy number variations and coding sequence variants, involving more than 100 genes, have been found in patients with ASD. Studying SHANK 3 gene CNVs and its associated phenotype in ASD patients might provide guidance for future treatment and intervention of ASD. The studied ASD children displayed sensory processing problems. SHANK3 copy number gains were found in three cases and it signifies the gene dosage effect of SHANK3 in ASD pathogenesis. To the best of our knowledge, this is the sixth report of 22q13 duplication including SHANK3. Abstract: Background: Current estimates indicate that >80 % of children with autism spectrum disorder (ASD) exhibit concomitant sensory processing problems and hyper- or hypo-reactivity to sensory input. These are now included as diagnostic criteria for ASD in the Diagnostic and Statistical Manual of Mental Disorders—Fifth Edition. Chromosomal rearrangements, copy number variations (CNVs), and coding sequence variants involving >100 genes have been identified in patients with ASD. Studying the CNVs of one such gene, SHANK3, and the associated phenotype in patients with ASD could provide insights that will guide future ASD treatments and interventions. Objective: To assess SHANK3 CNVs in children with ASD and investigate their sensory processing patterns using the Short Sensory Profile (SSP). Subjects and methods: Forty children with ASD were assessed using the Autism Diagnostic Interview-Revised. SSP was used to evaluate atypical sensory behavior, e.g., hyper- or hypo-reactivity to sensory input or unusual sensory interests. SHANK3 CNVs were assessed in these children using Multiplex Ligation-dependent Probe Amplification. Results: Of the 40 cases, 77.5 % showed sensory reactivity symptoms. The greatest difference from normality was observed in the under-responsive/seeks sensation domain, followed by the tactile sensitivity domain, whereas hypo-activity (low-energy/weak domain) was closest to normal. The sensory reactivity symptoms were significantly correlated with the severity of ASD. However, only three of the 40 cases had de novo duplications at 22q13.33. The duplications included SHANK3 in two of the cases and only the distal flanking region of SHANK3 in the third case. All three duplication cases also showed symptoms associated with the low-energy/weak domain. Conclusion: We found that children with ASD exhibited sensory processing problems. The SHANK3 copy number gains found demonstrate the gene dosage effect of SHANK3 in ASD pathogenesis. This study adds to the growing understanding of 22q13 duplications that include SHANK3.